Upaya Meningkatkan Social Attitude Melalui Model Pembelajaran Value Clarification Technique (VCT) Pada Mata Pelajaran Akidah Akhlak Kelas VIII Pondok Pesantren Modern Babussalam Teluk Bakung - Indah Fadila, Ahmad Sanusi Luqman, Nurmisda Ramayani (Khazanah : Journal of Islamic Studies, 2022)
The Value Clarification Technique (VCT) learning model is a variable that is used to improve the social at titude of class VIII students at the Babussalam Modern Islamic Boarding School, Teluk Bakung. The subjects of this study were 24 class VIII students of Babussalam Modern Islamic Boarding School. This research was conducted in two cycles, where each cycle consisted of four stages, namely planning, action, observing, and reflection. Using qualitative descriptive analysis techniques. Before conducting action research, it begins with the pre-cycle stage, at this stage the researcher makes observations about the results of the evaluation of Akhlak Aqidah learning. From the analysis of the data that the researchers obtained, it was known that the initial conditions were that in class VIII there were problems, namely the social attitude of students in learning Aqidah Akhlak was low and they did not reach the KKM 75 target set by the madrasah. In the pre-cycle implementation, the average score of students with learning mastery (57.5%) was obtained. Then carried out the first cycle, from the classroom action research data that the researchers found there was an increase in the average score in the first cycle with a learning completeness score (58.75%), but there were still many students who had not achieved completeness. Continued to cycle II action, in this action there was a significant increase, namely the completeness of learning outcomes (88.75%). This shows that the Value Clarification Technique (VCT) learning model that the researchers used was able to improve students' social attitudes in the Akidah Akhlak subject, even though it had not yet reached 100%.